Evaluation of temperature and healing in treatment of gingival enlargement using different gingivectomy techniques: A randomized controlled clinical study (Annals of Medical Research, 2021)
Aim: Gingival enlargement comprises a common feature of gingival disease in which an increase in size of the gingiva is observed which may result from chronic or acute inflammatory changes. The aim of this study was to compare and investigate epithelization, gingival temperature, inflammation and pain levels in post-operative healing process in 4 different gingivectomy techniques including Er:YAG laser, Nd:YAG laser, electrocautery and conventional gingivectomy in treatment of chronic inflammatory gingival enlargements. Material and Methods: Our split-mouth designed study was conducted on 37 systemically patients consisting of 19 females and 18 males, who had gingival enlargement areas on maxillar and mandibular anterior regions. Clinical periodontal parameters, gingival crevicular fluid (GCF) levels and gingival temperature levels were recorded before the investigation and during gingivectomy operations with different techniques, gingival temperature was measured. Gingival temperature and epithelization levels in 3, 7, 10 and 15 days; GCF levels in 15, 30 and 90 days and pain levels in 2, 8 hours and between 1-7 days of post-operative healing process were evaluated.Results: When clinical periodontal parameters were compared, there was no significant difference found between all application within and between groups (p>0.05). When gingival temperature during operations were compared, there was a significant difference between all application groups (p0.05). In 15 days, there was a significant difference between Nd:YAG laser group and the other groups (p0.05). There were a significant difference in epithelization and pain levels in all applications between groups by time (p0.05).Conclusion: It was found that Er:YAG laser assisted gingivectomy technique which has better epithelization rates and rapidity, lower pain levels and no thermal damage effects in tissues, is more advantageous than other techniques.
Keywords: Electrosurgery; gingival enlargement; gingivectomy; laser; temperature